Design of an Orbital Infrastructure to Guarantee Continuous Communication to the Lunar South Pole Region - Trabacchin, Nicolò; Colombatti, Giacomo (Aerospace, 2025)
The lunar south pole has gained significant attention due to its unique scientific value and potential for supporting future human exploration. Its potential water ice reservoirs and favourable conditions for long-term habitation make it a strategic target for upcoming space missions. This has led to a continuous increase in missions towards the Moon thanks mainly to the boost provided by NASA’s Artemis programme. This study focuses on designing a satellite constellation to provide communication coverage for the lunar south pole. Among the various cislunar orbits analysed, the halo orbit families near Earth–Moon Lagrangian points L1 and L2 emerged as the most suitable ones for ensuring continuous communication while minimising the number of satellites required. These orbits, first described by Farquhar in 1966, allow spacecraft to maintain constant communication with Earth due to their unique geometric properties. The candidate orbits were initially implemented in MATLAB using the Circular Restricted Three-Body Problem (CR3BP) to analyse their main features such as stability, periodicity, and coverage time percentage. In order to develop a more detailed and realistic scenario, the obtained initial conditions were refined using a full ephemeris model, incorporating a ground station located near the Connecting Ridge Extension to evaluate communication performance depending on the minimum elevation angle of the antenna. Different multi-body constellations were propagated; however, the constellation consisting of three satellites around L2 and a single satellite around L1 turned out to be the one that best matches the coverage requirements.